Burden of orofacial clefts from 1990–2021 at global, regional, and national levels - Qinqin Ma; Qinqin Ma; Jie Wei; Jie Wei; Jie Wei; Bo Peng; Bo Peng; Bo Peng; Jianying Liu; Jianying Liu; Shuixue Mo; Shuixue Mo (Frontiers in Pediatrics)
ObjectivesWe aimed to study and comprehensively evaluate the burden of OFCs at global, regional, and national levels.MethodsBased on data from the Global Burden of Disease database for 2021, we analysed the prevalence, mortality, and disability-adjusted life years (DALYs) of orofacial clefts (OFCs) from 1990–2021, categorised by sex, regions, and sociodemographic index (SDI). Numbers and age-standardised rates (ASRs) of the aforementioned indices were estimated through a systematic analysis of modelled data from the GBD 2021 study. Finally, the relationship between SDI and the epidemiological parameters of OFCs was evaluated.ResultsIn 2021, the global prevalence of OFCs included 4,124,007 cases, resulting in 1,719 deaths and 408,775 DALYs. From 1990–2021, prevalence cases decreased by 40.38%, while mortality rates, and DALYs decreased by 86.08%, and 68.33%, respectively. Moreover, the ASRs for prevalence, mortality, and DALYs demonstrated a decreasing trend during the period. In 2021, the highest age-standardised prevalence rates (ASPRs) of OFCs were recorded in South Asia, North Africa, the Middle East, and Central Asia. Nationally, Palestine, Qatar, and Bangladesh reported the three highest ASPRs in 2021. A nonlinear association was observed between the ASRs of OFCs and the SDI at regional and national levels.ConclusionsThe global burden of OFCs decreased from 1990–2021. However, there is a disparity in disease burden across different regions, over 80% of the burden is borne by patients in low- and middle-income countries, the burden of OFCs remains a major public health challenge globally. Our findings will help to formulate appropriate policies to reduce the OFCs burden.